DEM modeling of the effects of external loads and material properties on the stability of nickel ore in a cargo hold. (December 2021) - Zhang, Jianwei; Wang, Zhanwei; Lu, Jinshu; Ju, Lei; Chen, Gechuan
Abstract: Cargo liquefaction leading to the serious loss of ship stability is attracting more attention from the international community. However, due to the complexity of external loads and the properties of the cargo, the mechanism of cargo liquefaction has not been revealed for every situation. In this study, considering the effects of the moisture content, particle size grading, initial porosity and motions of a typical cargo hold, a three-dimensional full-scale numerical model based on the discrete element method is established, and numerical investigations are carried out. To better ensure that the full-scale model conditions are consistent with the reality and the rationality of particle amplification, a static incline test and a cargo loading test are also simulated and verified. The results show that the effect of the moisture content on the cargo stability can be estimated using the friction coefficients between particles. Additionally, the moisture content is the key factor that affects the stability of the cargo and promotes its liquefaction. Furthermore, there are critical values for fine particle content, at which cargo fluidity is greatly enhanced. For external loads, the cargo stability is greatly weakened with the increase of the motion amplitude. Furthermore, there is a critical frequency, beyond which the cargo stability will be further damaged.